2019
DOI: 10.1111/ijpp.12574
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of patient safety culture in Kuwait hospitals: a qualitative study of healthcare professionals' perspectives

Abstract: Objective Patient safety culture (PSC) represents a key component of the quality of care offered by healthcare professionals. Therefore, it is crucial to understand the factors that influence the implementation of a safe culture. This study explored the knowledge and attitudes of healthcare professionals in Kuwait towards the factors that might affect the PSC. Methods A qualitative study using semi‐structured interviews with healthcare professionals was conducted between February and June 2018 at two major hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 28 publications
5
18
0
2
Order By: Relevance
“…The current staff members' perspectives were similar to those reported by a recent qualitative study conducted in two accredited public hospitals in Kuwait. 5 For example, both studies suggested that patient safety was not prioritised in daily practice due to staff and resource shortages. However, unlike that study, the staff and patients in the current study suggested more training and orientation to improve staff awareness of patient safety.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current staff members' perspectives were similar to those reported by a recent qualitative study conducted in two accredited public hospitals in Kuwait. 5 For example, both studies suggested that patient safety was not prioritised in daily practice due to staff and resource shortages. However, unlike that study, the staff and patients in the current study suggested more training and orientation to improve staff awareness of patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in findings may be attributed to accountability differences between the two settings-the hospitals studied by Al Hamid et al were accredited, while the hospital in the current study was not. 5 Another difference of note involved the presence (or lack thereof ) of supportive leadership. Whether by implementing an accreditation programme, offering supportive leadership or targeting other factors, it seems that healthcare organisations with a positive PSC have mechanisms that support decisive action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 10 ] The impact of the introduction of a rational Drug Use Policy in Thailand, with a positive impact on the unsafe prescribing of glibenclamide, is described in another paper [ 11 ] and a study from Kuwait highlights that issues related to support, staffing, resources and response to error were perceived as important barriers to developing a strong patient safety culture. [ 12 ]…”
Section: Figurementioning
confidence: 99%